KOMPLEKS MAKAM TUA KAMPUNG LAMA TAMOSI DESA LOKA KECAMATAN TIRAWUTA KABUPATEN KOLAKA TIMUR - Yusma Yusma; abdul alim; salniwati salniwati (SANGIA: Jurnal Penelitian Arkeologi, 2020)
This research user descriptive qualitative research. The data collection stage was through literature study and field observations. Analysis of research data using morphological analysis, contextual analysis. Based on research results, the Old Tamosi Old Village Complex Dining Site had a rectangular shape consisting of jirat and headstone. The grave is made of river stone that is not patterned or decorated. The Old Tomb Site of Old Tamosi Village had 16 tombs consisting of 15 Islamic tombs and 1 megalithic tomb, 2 tombs have a tomb and headstone and 14 tombs have a tomb without a tombstone. Some tombs are influenced by Islamic and Pre-Islamic elements, visible megalithic elements and megaitic Islamic elements marked by tombs that have a northwest-facing tomb. Tombstones and jirat which are above jirat not added ornaments. From the forms of the tomb can be described Simbune village community already has the characteristics of Islamic and megalithic culture. Keywords: Old tomb, Tamosi, shape, cultural elements.